Causal attributions and perceived stigma for myalgic encephalomyelitis/chronic fatigue syndrome. (September 2022) - Froehlich, Laura; Hattesohl, Daniel BR; Cotler, Joseph; Jason, Leonard A; Scheibenbogen, Carmen; Behrends, Uta
Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) is a chronic disease with the hallmark symptom of post-exertional malaise. Evidence for physiological causes is converging, however, currently no diagnostic test or biomarker is available. People with ME/CFS experience stigmatization, including the perception that the disease is psychosomatic. In a sample of 499 participants with self-diagnosed ME/CFS, we investigated perceived stigma as a pathway through which perceived others' causal attributions relate to lower satisfaction with social roles and activities and functional status. Higher perceived attributions by others to controllable and unstable causes predicted lower health-related and social outcomes via higher perceived stigma.